2020
DOI: 10.3390/diagnostics10110909
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Biomarkers Urinary KIM-1 and YKL-40 for Early Diabetic Nephropathy, in Patients with Type 2 Diabetes: A Systematic Review and Meta-Analysis

Abstract: There is a lack of prediction markers for early diabetic nephropathy (DN) in patients with type 2 diabetes mellitus (T2DM). The aim of this systematic review and meta-analysis was to evaluate the performance of two promising biomarkers, urinary kidney injury molecule 1 (uKIM-1) and Chitinase-3-like protein 1 (YKL-40) in the diagnosis of early diabetic nephropathy in type 2 diabetic patients. A comprehensive search was performed on PubMed by two reviewers until May 2020. For each study, a 2 × 2 contingency tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Kidney injury molecule-1 (KIM-1) is a type 1 epithelial transmembrane glycoprotein, and its expression is upregulated in the proximal tubules of the kidney following an ischemic insult [ 20 ]. Patients with diabetic nephropathy have higher KIM-1 levels than controls [ 5 , 21 , 22 , 23 ]. Moreover, KIM-1 levels correlate with GFR and urinary albumin excretion [ 5 , 8 , 24 , 25 , 26 ].…”
Section: Kidney Injury Moleculementioning
confidence: 99%
“…Kidney injury molecule-1 (KIM-1) is a type 1 epithelial transmembrane glycoprotein, and its expression is upregulated in the proximal tubules of the kidney following an ischemic insult [ 20 ]. Patients with diabetic nephropathy have higher KIM-1 levels than controls [ 5 , 21 , 22 , 23 ]. Moreover, KIM-1 levels correlate with GFR and urinary albumin excretion [ 5 , 8 , 24 , 25 , 26 ].…”
Section: Kidney Injury Moleculementioning
confidence: 99%
“…Serum YKL-40 levels were significantly increased in the group with persistent proteinuria compared with those in the other groups and correlated with the urinary albumin/creatinine ratio ( 64 ). Similarly, the level of YKL-40 was found to be increased in the early stage of DN and was correlated DN progression ( 65 , 66 ). These findings suggest that YKL-40 may be used as a diagnostic indicator for early-stage of DN.…”
Section: Myokines and Dnmentioning
confidence: 84%
“…A study revealed that patients who underwent peritoneal dialysis and hemodialysis had elevated levels of YKL-40 when compared to healthy individuals. YKL-40 is a predictor of diabetic nephropathy with a sensitivity of 83% and specificity of 85% (24). Elevated levels of YKL-40 measured by ELISA in patients with different stages of CKD.…”
Section: Biomarkers Of Adaptive Repair and Fibrosismentioning
confidence: 99%